Evaluation of Sustainable and Analysis of Influencing Factors for Agriculture Sector: Evidence From Jiangsu Province, China - Wang, Zhiguo; Huang, Lufei; Yin, Linsen; Wang, Zhixiong; Zheng, Dandan (Frontiers in Environmental Science, 2022)
Sustainable agriculture is a vital part of the UN Sustainable Development Goals. While tremendous achievements in the agriculture sector in China have been made, a series of problems are challenging the sustainable development of the agriculture management and agriculture economy. In this paper, the level of sustainable agriculture development was evaluated by constructing an entropy-TOPSIS model. The sustainable agricultural development level evaluation system was subsequently established, including 4 first-level criteria (economy, society, environment and resources) and 25 second-level criteria. Corresponding data on 13 cities in Jiangsu Province, China (from 2016 to 2019) were collected. Moreover, the main obstacle factors restricting the sustainable agriculture development level were analyzed through the obstacle diagnosis model. The Tobit regression model was established for an empirical study on its influencing factors. The results showed that the agricultural sustainable development level in Jiangsu Province is going upward, and the development level gaps between various prefecture-level cities are narrowing; the output values in agriculture, forestry, animal husbandry and fishery services, per capita disposable income of farmers and other aspects are the main obstacle factors for agricultural sustainable development. The research objective of this paper was to improve the index system of agricultural sustainable development, analyze the influencing mechanism and obstacle factors, and explore the promotion path of agricultural sustainable development in Jiangsu by optimizing the spatial layout. The main innovation of this paper was bringing the five interrelated and interactive dimensions of “economy, society, environment, ecology, and resources” into the same analytical framework to analyze the concept and connotation of agricultural sustainable development.